2020
DOI: 10.1088/1755-1315/454/1/012113
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and sensory characteristics of sweet bun produced from wheat and purple sweet potato flour

Abstract: This study was carried out to investigate the physicochemical and sensory characteristics of sweet bun as affected by the ratio of wheat flour (WF) and purple sweet potato flour (PSPF). Six samples of breads were made from WF and PSPF in various ratio namely P1 (100% wheat flour), P2 (80:20), P3 (60:40), P4 (40:60), P5 (20:80), and P6 (100% PSP flour). The results showed that the ratio of WF and PSPF had significant effect (P < 0.05) on the colour value (L, a, b, and ºhue), browning index, specific volume, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…found that the PSPA increased the firmness and elasticity of jelly (Park & Park, 2012). In addition, previous studies have shown that the addition of PSPA can significantly improve the taste and texture of bread (Lee & Park, 2011), cookies (Liu et al ., 2013), noodles (Lee, 2012) and bun (Zhu & Sun, 2019; Aritonang et al ., 2020), making them more popular with consumers.…”
Section: Introductionmentioning
confidence: 99%
“…found that the PSPA increased the firmness and elasticity of jelly (Park & Park, 2012). In addition, previous studies have shown that the addition of PSPA can significantly improve the taste and texture of bread (Lee & Park, 2011), cookies (Liu et al ., 2013), noodles (Lee, 2012) and bun (Zhu & Sun, 2019; Aritonang et al ., 2020), making them more popular with consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Chikpah et al [ 92 ] summarized that the color changes are attributed to the differences in baking time and temperature, addition ratios, and the concentrations of phytochemicals like anthocyanins and β-carotenes in the SPF samples. Furthermore, increasing the addition ratios of SPF to wheat flour does not always increase the a* and b* compared to the control samples as reported by Aritonang et al [ 23 ] and Singh et al [ 93 ]. Where Singh et al [ 93 ] stated cookies prepared with 100% wheat flour or wheat-SPF 80:20% showed no significant differences in redness or yellowness.…”
Section: Resultsmentioning
confidence: 59%
“…Where Singh et al [ 93 ] stated cookies prepared with 100% wheat flour or wheat-SPF 80:20% showed no significant differences in redness or yellowness. Furthermore, Aritonang et al [ 23 ] reported that the increase in the addition ratio from 80:20% to 60:40% wheat-SPF had no significant effect on the redness of the sweet bun.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mocaf are made from cassava tubers that are fermented using lactic acid bacteria and have different increased viscosity, glassing ability, rehydration capacity, WHC, and solubility better than cassava flours [4]. Purple sweet potatoes flours are widely used as ingredient for extrusion products such as snack, noodle, artificial rice, due to it contains many nutrients such as anthocyanins and dietary fibres which is good for human health as reducing blood sugar, obesity, and colon cancer [5]. Extrusion processing is a method that can simplify the process of mixing, moulding, and cooking into one simultaneous step of the process to produce food products [6].…”
Section: Introductionmentioning
confidence: 99%